Effect of Angelica polysaccharide on mouse myeloid-derived suppressor cells - Shen, Jie; Zhang, Mengyu; Zhang, Ke; Qin, Yahan; Liu, Meifang; Liang, Shujuan; Chen, Daquan; Peng, Meiyu (Frontiers in Immunology, 2022)
Angelica polysaccharide (APS) is a polysaccharide extracted from Angelica sinensis, which is one of the main active components of Angelica sinensis. Many studies have demonstrated that APS can promote the activation and function of a variety of immune cells and is recognized as an immune enhancer, but the regulatory effect of APS on myeloid-derived suppressor cells (MDSC) is still unclear. In this study, we investigated the effects of APS on MDSC proliferation, differentiation and function through in vivo and in vitro. In vitro, our results showed that APS promoted the proliferation, differentiation and immunosuppressive function of MDSC through STAT1 and STAT3 signaling pathways, and positively correlated with the expression level of Mannose receptor (MR, also known as CD206) and in a concentration-dependent manner on APS. In vivo, APS up-regulated T cells, γδT cells, CD8+T cells, NK cells, monocytes/macrophages, and granulocytes in the peripheral blood and spleen of mice to varying degrees and was accompanied by the same degree increase in the proportion of MDSC. That reminds clinical application of APS treatment should pay attention to its possible side effects of increasing the quantity and function of MDSC, in order to increase its efficacy.